An innovative thermal management method for cooling loop of electric driving system for durable and high efficiency electric vehicle. (August 2021) - Li, Dongjun; Zhang, Caizhi; Fan, Ruijia; Xu, Lei; Wang, Yi; Guo, Wenjun; Chen, Jinrui; Ni, Meng
Highlights: Proposed an innovative framework with matched control strategies for loop of electric drive. Comparing performance differences between two frameworks of loop of electric drive. Realized refined thermal management targets of cooling loop of electric drive. Reduced energy consumption of pump and fan. Abstract: This paper proposed an innovative thermal management framework and its control strategies for the cooling loop of electric drive to achieve a more refined thermal management. To investigate the performance of this method used in EVs, the proposed innovative framework model and the conventional framework of the cooling loop of electric drive were developed in KULI based on the heating principle and heat transfer theory. And the rule-based control strategies were established in MATLAB/Simulink, which was set as a controller to regulate fan, pump and proportional valve. Then, the cooling performance and the energy consumption of the two frameworks were compared through co-simulation under steady-state and transient conditions of high temperature. The results showed that this method has a better performance in temperature control of key components (exit temperature of motor is reduced by at least 5.0 °C under 3 steady-stage simulation conditions) and improved efficiency of the pump (from 6.4% to 10.1% in mode 1, from 15.2% to 23.6% in mode 2, and from 21.4% to 36.8% in mode 3), which is useful to achieve long lifetime and high efficiency of electric vehicles.